NahW, a Novel, Inducible Salicylate Hydroxylase Involved in Mineralization of Naphthalene by Pseudomonas stutzeri AN10 - Bosch, Rafael (American Society for Microbiology, 1999)
Two genes, nahG and nahW, encoding two independent salicylate 1-hydroxylases have been identified in the naphthalene-degrading strain Pseudomonas stutzeri AN10. While nahG resides in the same transcriptional unit as the meta-cleavage pathway genes, forming the naphthalene degradation lower pathway, nahW is situated outside but in close proximity to this transcriptional unit. The nahG and nahW genes of P. stutzeri AN10 are induced and expressed upon incubation with salicylate, and the enzymes that are encoded, NahG and NahW, are involved in naphthalene and salicylate metabolism. Both genes, nahG and nahW, have been cloned in Escherichia coli JM109. The overexpression of these genes yields peptides with apparent molecular masses of 46 kDa (NahG) and 43 kDa (NahW), respectively. Both enzymes exhibit broad substrate specificities and metabolize salicylate, methylsalicylates, and chlorosalicylates. However, the relative rates by which the substituted analogs are transformed differ considerably.